2019
DOI: 10.1002/hep.30671
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA MAT2B Promotes Glycolysis and Malignancy of Hepatocellular Carcinoma Through the miR‐338‐3p/PKM2 Axis Under Hypoxic Stress

Abstract: Glucose metabolism reprogramming, which is a well‐established characteristic of multiple cancers, demands a higher rate of glycolysis to meet the increasing demands for macromolecular synthesis and to maintain rapid proliferation in a hypoxic environment. However, the mechanism underlying this switch remains to be elucidated. In this study, we investigated the function of circular RNA MAT2B (circMAT2B) in hepatocellular carcinoma (HCC) glucose metabolism reprogramming and malignancy. CircMAT2B was identified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
186
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(196 citation statements)
references
References 31 publications
6
186
0
4
Order By: Relevance
“…For example, circHIPK3 up-regulated BDNF expression by competitively binding with miR-107, thus facilitating cell viability and migration in gastric cancer [18]. CircMAT2B induced the glycolysis and malignancy in hepatocellular carcinoma via regulating PKM2 through sponging miR-338-3p [19]. Therefore, circRNAs are involved in the regulation of cell malignant phenotypes and metabolism, thus affecting the occurrence and development of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, circHIPK3 up-regulated BDNF expression by competitively binding with miR-107, thus facilitating cell viability and migration in gastric cancer [18]. CircMAT2B induced the glycolysis and malignancy in hepatocellular carcinoma via regulating PKM2 through sponging miR-338-3p [19]. Therefore, circRNAs are involved in the regulation of cell malignant phenotypes and metabolism, thus affecting the occurrence and development of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Sponging miRNA is one of the most common regulatory mechanisms of circRNA. For example, circRNA CircFAT1 promotes the expression of YAP in osteosarcoma cells via sponging miR‐375 26 ; circRNA MAT2B promotes glycolysis and malignancy of hepatocellular carcinoma via sponging miR‐338‐3p under hypoxic stress 27 ; circRNA circ‐BANP promotes lung cancer progression via sponging miR‐503 28 . In the current work, we identified that the expression of circ_POLA2 was increased in lung cancer and high level of circ_POLA2 was negatively associated with the prognosis.…”
Section: Resultsmentioning
confidence: 60%
“…Alteration of energy metabolism, especially abnormal activation of the glycolysis pathway was observed in diverse human cancers (26,27). circRNAs are reported to be involved in the regulation of the Warburg effect in human cancers (28,29). Hence, the level of EcAR were checked in NScLc cells and it was found that circ-ACACA silencing reduced the glycolysis rate.…”
Section: Discussionmentioning
confidence: 99%